Tourism destination selection attributes, tourist satisfaction and behavioral intentions of multicultural families in South Korea: Focusing on self-efficacy - Chen Ling; Woo-Jin Shin; Alan Brown (Global Business & Finance Review (GBFR), 2024)
Purpose: Empirically analyze the tourism destination selection attributes, tourist satisfaction and behavioral intentions of multicultural families by country of origin. Confirm the mediating effect of self-efficacy on the relationship between tourism destination selection attributes, tourist satisfaction and behavioral intentions. Design/methodology/approach: Survey among adult multicultural family members in the Gwangju and Jeonnam regions of South Korea. The main analysis methods were confirmatory factor Structural Equation Modeling analysis. Findings: Behaviors and preferences differed depending on the country of origin of the respondents, and were influenced by tourism destination selection attributes. To promote cultural exchange and understanding, the local community should support activities that foster cultural exchanges and understanding between multicultural families and residents, along with education programs to promote the independence and social participation of multicultural families. Research limitations/implications: The study focused only on multicultural family members from three countries, limiting its generalizability to all multicultural populations. Future research on the position of vulnerable populations in tourism, and the economic effects of their tourism is recommended. Originality/value: By focusing on the experiences of multicultural family members, this research fills a gap on tourism for multicultural families living in Korea, placing an emphasis on self-efficacy, which has been overlooked in previous studies. Also, by comparing and analyzing the relationships between self-efficacy and the tourism behavioral intentions and satisfaction of families originating from China, Vietnam, and the Philippines, this research demonstrates how the psychological characteristics of multicultural families influence diverse tourism experiences.
Keywords: 650; Multicultural Families; Tourism Destination Selection Attributes; Self-Efficacy; Tourist Satisfaction; Behavioral Intention